Determinan Fraudulent Financial Reporting Using Fraud Pentagon Analysis - Fidyah Quraini; Yuni Rimawati (JAFFA, 2018)
This research aimed at knowing factors of fraudulent financial reporting using pentagon fraud analysis. This research analyzed the influence of financial target, financial stability, external pressure, institutional ownership, ineffective monitoring, quality of external auditors, change of auditors, change of directors, and number of CEO’s picture in fraudulent financial report. Sample in this research were 14 go public government companies from 2013 to 2017. Source of data in this research were secondary data in form of annual report in official website of Indonesia Stock Exchange. The examination of this research used logistic regression. The result of this study showed that the influence of external pressure expected fraudulent financial report, while financial target, financial stability, institutional ownership, ineffective monitoring, quality of external auditors, changing auditors, changing directors, and a number of CEO’s picture often did not influence the fraudulent financial reporting.